The utilization of organic waste into fermented goat fodder in Tanjung Rejo village, Deli Serdang regency - Yeanny, Mayang Sari; Yurnaliza; Hannum, Saleha (Talenta Publisher, 2019)
Community service activities with the title of The Utilization of Organic Waste into Fermented Goat Fodder in Tanjung Rejo Village, Deli Serdang Regency will be held in May - November 2019.The purpose of this community service is to utilize organic waste into fermented goat fodder in Tanjung Rejo village.Organic waste such as straw, banana tree and others can be converted into fermented goat fodder which is economical, nutritious and environmentally friendly.The specific target of this community service is that the fermented goat fodder produced can be stored for a long time with good quality.The method used is a combination of counselling, training, hands-on practice and work evaluation.The procedures of making fermented goat fodder are as follows; (1) Chop straw or banana tree using a chopper machine, this stage serves to make the fermentation process easier. (2) Prepare the place of manufacture, can use tarpaulins, large plastic or large barrels (3). Dissolve sugar or sugar cane with water plus SOC-HCS probiotic solution. (4) Enter the straw, husk and bran at the place of preparation that has been prepared previously. (5) Flush all materials that have been arranged evenly in the place of manufacture with a solution of sugar and SOC-HCS that had been dissolved with water. (6) Mix all ingredients evenly. (7) After everything has been stirred evenly, then cover the place of manufacture with a tarp or with anything, make sure to be airtight. (8) Wait for 1 - 14 days. The fermented fodder that you have made from straw will be ready or if the fermentation feed is made using a banana tree, it can be faster.All products produced can be used for their own needs or sold according to the needs of the people of Tanjung Rejo village, especially the Tanjung Rejo goat breeders group.